Determinasi Nonklinis dalam Perkembangan Polineuropati/Neuropati Diabetik di Indonesia: Systematic Literature Review - Susanti Dwi Ariani; I Nyoman Ehrich Lister; Chrismis Novalinda Ginting; Ali Napiah Nasution; Dodik Tugasworo Pramukarso; Surya Hajar Fitria Dana; Syaiful Ramadhan Harahap (Pelantar Press, 2025)
This systematic literature review aimed to identify and synthesize nonclinical determinants contributing to the risk and management of diabetic peripheral neuropathy (DPN) in patients with type 2 diabetes mellitus (T2DM) in Indonesia. This review followed the PRISMA 2020 guidelines and included ten eligible studies published between 2021 and 2025. The analysis revealed that various nonclinical factors—including sociodemographic (age, education level, rural-urban disparity), behavioral (smoking, physical inactivity, poor self-monitoring), psychosocial (low risk perception, limited family support, emotional distress), and anthropometric-vascular indicators (high BMI, uncontrolled blood pressure, low ABI)—significantly affect DPN risk and severity. In addition, system-level factors, such as health service accessibility and national NCD control policies, influenced early detection and complication management. These findings highlight the need for an integrative, multidisciplinary approach to DPN prevention and intervention that goes beyond clinical care. Strengthening community-based health education, incorporating psychosocial support in primary care, and formulating socially responsive health policies are essential to reduce the DPN burden among the diabetic population in Indonesia